Memberdayakan Masyarakat Lewat Penyiaran Berita Bencana Alam - Ana Nadhya Abrar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2008)
In reporting natural disaster, the press should empower audiences. How the press should shape the news in order to empower audiences? Departure from literatures review, this article suggests several guidelines, namely: (i) pushing audiences thinking creatively; (ii) avoiding “news maker authorities”; (iii) avoiding influence of bureaucrat and foundation institution; (iv) creating discourses carefully; (v) explaining risks after having natural disaster; and (vi) helping audiences define fear feeling correctly.